Abdominal wall reconstruction: Strategies to enhance outcomes. Issue 6 (30th November 2015) - Nahabedian, Maurice Y.; Nahabedian, Anissa G.
Abstract : Learn about the various strategies for preoperative optimization, intraoperative technical innovations, and postoperative care that were developed to assist with enhancing surgical outcomes following abdominal wall reconstruction.